A New Concept of an Air-Electrode Catalyst for Li2O2 Decomposition Using MnO2 Nanosheets on Rechargeable Li-O2 Batteries. (20th October 2017) - Saito, Morihiro; Kosaka, Shinpei; Fujinami, Taichi; Tachikawa, Yusuke; Shiroishi, Hidenobu; Streich, D.; Berg, E.J.; Novák, Petr; Seki, Shiro
Abstract: To improve the charge/discharge properties of a rechargeable Li-O2 battery (LAB), we synthesized a new air-electrode catalyst composed of MnO2 nanosheets (Mn-NSs) and Ketjen Black (KB), i.e., a KB-comp. Mn-NS catalyst. The composite catalyst was synthesized by electrostatically restacking the nanomaterials in a colloidal solution with Li + and its electro-catalytic activity as an air-electrode for a LAB test cell was evaluated. The KB-comp. Mn-NS catalyst exhibited excellent performance, especially for oxidation of Li2 O2 deposited on the surface of the air-electrode during the charging process, which led to enhanced reversibility of the Li2 O2 deposition/decomposition reaction during the discharging/charge cycles. Evidence of these reactions was investigated and confirmed by X-ray diffraction analysis and scanning electron microscopy-energy dispersive X-ray spectroscopy. The Li2 O2 was deposited and decomposed more homogeneously at the air-electrode with the KB-comp. Mn-NS catalyst than that with only KB. Consequently, the composite catalyst significantly reduced the overpotential and improved the cycleability up to the 27th cycle, even at 0.40 mA.